Socialization of Halal Digital Transformation Cold Chain Last Mile to Increase Company Transparency and Competitiveness - Lesmini, Lis; Rizaldy, Wynd; Marlita, Devi; Handayani, Sri; Indriyati (Universitas Nahdlatul Ulama Surabaya, 2025)
Digital transformation in the logistics sector, particularly in last-mile delivery services, plays a strategic role in improving efficiency, transparency, and consumer trust. In Indonesia, increasing awareness of halal products underscores the importance of halal traceability systems to ensure product compliance from upstream to end consumers. However, small and medium-sized last-mile delivery companies still face limited understanding, digital readiness, and implementation of technology-based halal traceability. This community service program aims to enhance halal literacy and digital capacity of partner companies affiliated with the Indonesian Halal Logistics Association (AHLI) through socialisation and assisted application of halal traceability principles. The program consisted of preparation, interactive training, and evaluation using pre-test and post-test instruments. The materials covered halal traceability principles, the SIHALAL system, segregation of halal and non-halal products, and the development of SOPs in accordance with current PPH and SJPH regulations. The program is expected to support the implementation of digitally enabled halal logistics, strengthen Muslim consumer trust, and promote a sustainable and inclusive halal supply chain aligned with the Indonesian Sharia Economy